ChemInform Abstract: Synthesis of 2‐Amino‐1, 3, 4‐oxadiazoles and 2‐Amino‐1, 3, 4‐thiadiazoles via Sequential Condensation and I2‐Mediated Oxidative C—O/C—S Bond Formation. Issue 23 (June 2015) - Niu, Pengfei; Kang, Jinfeng; Tian, Xianhai; Song, Lina; Liu, Hongxu; Wu, Jie; Yu, Wenquan; Chang, Junbiao
Abstract The transition metal free sequence allows a facile and generally high‐yielding approach to the title heterocycles with a use of aromatic, aliphatic, and cinnamic aldehyde reactants.